Implementasi Metode Waterfall untuk Membuat Antarmuka pada Aplikasi Koperasi Simpan Pinjam Berbasis Mobile - I Made Yadi Dharma; I Putu Hariyadi; Ahmat Adil; Heroe Santoso (Jurnal Teknologi Informasi dan Multimedia, 2024)
Current technological developments have penetrated various sectors of human daily activities, almost every human activity is supported by technology that functions to facilitate the completion of work, starting from things that seem trivial to quite complicated work. Therefore, Banjar Tri Parartha residents who have a business unit in the form of a savings and loan cooperative with funds from member contributions, run it by carrying out cooperative principles to help the economic movement of its citizens based on the principle of family. At this time the process of recording, calculating to the reporting process is still done conventionally, so that cooperative administrators are quite busy every time they make an accountability report that is carried out every year. By running the analysis and design process in the application creation stage using the waterfall method. So in the interface design it is adjusted to what is needed by the cooperative. It is hoped that this research can be a reference in making applications as the next stage. By using the application design starting from the recording stage, processing calculations and presenting reports, it is hoped that all stakeholders will find it easier to monitor and obtain cooperative financial information, so that the transparency of cooperative funds can provide certainty for its members.